PWE-200 The impact of bowel preparation on other colonoscopy quality indicators. (28th May 2012) - Butt, S K; Defoe, H; Besherdas, K
Abstract : Introduction: Poor quality of bowel preparation may be a major obstacle to the effectiveness of colonoscopy. Poor bowel preparation results in repeat of the procedure or shortening the interval of repeat scheduled procedure all of which increase the economic burden of the test. Quality indicators of colonoscopy are an important assessment of an endoscopy unit to fulfil for formal accreditation from JAG (Joint Advisory Group of Gastrointestinal Endoscopy). These indicators include the caecal intubation rate, adenoma detection rate and polyp retrieval rate. Poor quality bowel preparation may affect all of these quality indicators of colonoscopy. The impact on the quality of bowel preparation on completion of colonoscopy and polyp detection/retrieval was assessed in this study. Methods: To test the hypothesis that poor bowel preparation results in reduced caecal intubation, reduced adenoma detection and polyp retrieval rates. This was a retrospective analysis of all colonoscopies performed at a district general hospital in the North of London for 1-year from June 2009. The quality of bowel preparation was documented as good, satisfactory or poor. The caecal intubation rate, adenoma detection rate and polyp retrieval rate within each of the types of quality of bowel preparation was scrutinised. Results: A total of 1261 colonoscopies were performed in the study period. The caecal intubation rates were 94%, 86% and 82% for good, satisfactory and poor bowel preparation respectively. The polyp detection rate were 20%, 20% and 16% and polyp retrieval rate of 92%, 87% and 77% for good, satisfactory and poor bowel preparation respectively. Conclusion: Patients undergoing colonoscopy whose bowel preparation is poor have significantly lower rates of caecal intubation, polyp detection and polyp retrieval compared those with good bowel preparation. This study demonstrates the importance for units to endeavour to improve bowel preparation for patients undergoing colonoscopy to improve completeness of colonoscopy. While individual colonoscopist will look to improve their quality indicators of colonoscopy by safer sedation scores and improval in withdrawal times, the quality of bowel prep needs to be assessed by the unit. Competing interests: None declared.